A modified three-term conjugate gradient method for large –scale optimization - Zaydan B. Mohammed; Nazar K. Hussein; Zeyad M. Abdullah (Tikrit Journal of Pure Science, 2020)
We propose a three-term conjugate gradient method in this paper . The basic idea is to exploit the good properties of the BFGS update. Quasi – Newton method lies a good efficient numerical computational, so we suggested to be based on BFGS method. However, the descent condition and the global convergent is proven under Wolfe condition. The new algorithm is very effective e for solving the large – scale unconstrained optimization problem.